Development of a minangkabau culture-based educational game to improve children's reading readiness - Kaniska Kristianti; Delfi Eliza; Farida Mayar; Setiyo Utoyo (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study is motivated by the need to stimulate early childhood learning through culturally grounded educational games to improve reading readiness in kindergarten settings. The introduction of reading concepts through culturally familiar and engaging media is believed to support early literacy development in a more meaningful way. This study employed a Research and Development (R&D) methodology using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were Grade B students of TK Sani Ashilla, Padang City. A small group trial involved 10 children in one class, and a field trial involved 23 children across two classes. The findings indicate that the educational game product received a content expert validation score of 100% (Very Valid), a Minangkabau cultural expert validation score of 87% (Very Valid), and a media expert validation score of 73% (Valid). The practicality test yielded a score of 95.5% (Very Practical), while the effectiveness test yielded a score of 88.52% (Effective). Based on these results, the Minangkabau culture-based educational game is declared suitable for use as an instructional medium for early childhood reading readiness.